Surgical Management of Mandibular Central Incisors with Dumbbell Shaped Periapical Lesion: A Case Report - Roopadevi Garlapati; Bhuvan Shome Venigalla; Jayaprakash D. Patil; Thumu Jayaprakash; C. H. Krishna Chaitanya; Rama S. Kalluru (Hindawi Limited, 2014)
Dental traumatic injuries may affect the teeth and alveolar bone directly or indirectly. Pulpal necrosis and chronic and apical periodontitis with cystic changes are the most common sequelae of the dental traumatic injuries, if the teeth are not treated immediately. This case report focuses on the conventional and surgical management of mandibular central incisors. A twenty-four-year-old male patient presented with pain in the mandibular central incisors. Radiographic examination revealed mandibular central incisors with dumbbell shaped periapical lesion. After root canal treatment, parendodontic surgery was performed for mandibular central incisors. After one-year recall examination, the teeth were asymptomatic and periapical lesion had healed.